Momentum and funding conditions - Garcia-Feijoo, Luis; Jensen, Gerald R.; Jensen, Tyler K. (Journal of Banking & Finance, 2018)
We find evidence linking return momentum with macroeconomic conditions, namely, the funding environment. We show that winners outperform losers by a significant amount in restrictive funding states, while in expansive states, winners and losers perform similarly. This pattern is consistent with changing investor preferences for winners and losers following signaled shifts in funding availability. One plausible channel for this relation is the interaction between stock-level illiquidity and funding conditions. We find that liquidity risk is significantly priced during restrictive states, especially in loser stocks. Furthermore, loser stocks become more illiquid during restrictive conditions. Both effects help explain the relative performance difference between losers and winners across funding environments. Moreover, the funding environment influences the relationship between momentum and firm characteristics, after controlling for the influence of sentiment, market states and return dispersion. Overall, transitions in funding states appear to encourage investors to revise their factor pricing decisions, which produces inter-temporal variation in momentum.